Peran koperasi dalam mewujudkan perekonomian yang berkeadilan sosial - Revrisond Baswir (Universitas Islam Indonesia, 1997)
Inequality is a critical problem to Indonesian economy. Inequality is caused by natural, cultural, and structural factors. Since the beginning, the New Order tends to disregard inequality on economic structure. This article concludes that the problem solving of it should be matched with the cause. It is indeed government has been doing actions, but those actions are partial and charitable, even government tends to use those actions as a politic commodity. This article also concludes that to solve those problems, we should uphold the economic democracy. Idealistically, it can be upheld by maintaining cooperation. But, in fact, cooperation has been disappeared from the principles of Indonesian democracy. At this context, this article evaluates in what ways the government upholds cooperation as a movement of mass economy based on family atmosphere. As you will see, the solving key of this problem is on the restoration of the mass sovereignty as mandated by the constitution.